2008
DOI: 10.1111/j.1539-6924.2008.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

Ranking Nuclear and Radiological Terrorism Scenarios: The Italian Case

Abstract: A quantitative criterion for ranking the different scenarios of nuclear and radiological terrorism has been developed. The aim of the model is not to predict terroristic events but only to indicate which scenario has the higher utility from the point of view of a terroristic organization in terms of balance between factors favoring and discouraging the attack, respectively. All these factors were quantified according to a scoring system that takes into account the logarithmic relationship between perceptions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…It is interesting to investigate how the model described in the article and based on a simple circular geometry can be applied to more complex situations. For that reason a comparison was made between the simulation of a stadium‐concealed RED made in a previous study ( 3 ) and the equivalent geometry presented in this work. With reference to Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is interesting to investigate how the model described in the article and based on a simple circular geometry can be applied to more complex situations. For that reason a comparison was made between the simulation of a stadium‐concealed RED made in a previous study ( 3 ) and the equivalent geometry presented in this work. With reference to Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we used D th = 1 Gy, V = 3, and D 50 = 4.5 Gy. ( 3,4 ) The stochastic nature of survival can be taken into account by considering the individual susceptibility to the onset of deterministic effects, which may be expressed in terms of variability of both D th and D 50 . Current estimates of D th and D 50 range from 0.5 to 2 Gy and from 3 to 5 Gy, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that one of the most plausible scenarios involves a radiological attack. This scenario might entail weapons that produce a fission reaction (improvised nuclear device) or alternatively the scattering of radiological materials (radiological dispersion device, RDD), resulting in exposure and internalization of radioisotopes (Valentin 2005, Cassatt et al 2008, Tofani and Bartolozzi 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Recent events throughout the world underscore the growing threat of different forms of terrorism, including radiological terrorism (Durante and Manti 2002; Major 2002; Mettler and Voelz 2002; CRS 2004; Augustine et al 2005; González 2005; Bunn 2006; Dombroski and Fischbeck 2006; Tofani and Bartolozzi 2008). This has stimulated research on and development of medical countermeasures for protecting humans against radiation harm, including harm resulting from use by terrorist of a radioactivity dispersal device (RDD) (Goan 2001; NCRP 2001; FAO 2002; Ansari 2004; Scott 2005).…”
Section: Introductionmentioning
confidence: 99%